The Concept of Principal's Technology Competency in School Management Effectiveness - Nugroho Widi Susanto; Dina Hermina; Nurjani Nurjani (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the concept of school principals' technological competence and its role in the effectiveness of school management in the digital era. Using a qualitative research method with a literature review approach, the study identifies the concepts of school principals' technological competency, the indicators of this competency, and its relationship with the effectiveness of school management. The analysis results reveal three fundamental components of principals' technological competences: digital literacy, technological literacy, and human literacy, which principal’s must possess as a foundation to support their leadership duties in the digital era. These competencies are significantly influence the effectiveness of school management, such as efficient and effective administration, innovative technology-based learning, precise and rapid data-driven decision-making, transparency and accountability in school management, effective and productive school communication, and flexible, effective, collaborative, and globally of professional teacher development.